(3TQM GdeaUds - (3eLghds
(3ChdgG (B:s
(3HSe Gddg GdMQef GdQMje QH Jee HGdNjQ hHYO aEf Yde GdEYQGH Edi GdYdhe GdESdGejI Sde hCf cJGH GdeaUd Cf CaJM dge GdeZdb Edi Mdg bhdg Gddg CMeO bOe eaYhd CMeO hEf cGfJ QJHI GdeaYhd Cf jbY HYO QJHJi s
(3BNQgG (B:s
(3hgPg GdEHOGdGJ deG PcQfG Cf GdjGA CNa ef GdhGh hCdMbg eWdhHI ai fMh HjI CUdg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdfMhs